Tuesday

March 31, 2015

March 31, 2015

Posted by **Tashanna** on Sunday, August 12, 2007 at 4:50pm.

y-x=-4

For an algebraicc solution, show your work here.

y=x^2-6x+6

y-x= -4

Let's substitute x-4 for y in the first equation.

x-4 = x^2-6x+6

x^2 -7x + 10 = 0

(x-5)(x-2) = 0

x = 5 or 2

y = 1 (where x=5) or -2 (where x=2)

**Answer this Question**

**Related Questions**

How do I do this.?(Math.) - Use the Substitution method to solve the system of ...

Pre-Calculus - If you solve the following system of equations by substitution, ...

Differential Equations - Consider the spring - mass system, shown in Figure 4.2....

math - How do you solve system of equations and tell if they're consistant and ...

math - Solve the following algebraically. Trial and error is not an appropriate ...

math - solve the system algebraically and graphically 32x^2+9y^2=324 3y^2-x^2=3

Pre-Calculus/Trigonometry - Solve the following system of equations ...

Pre-Calculus/Trigonometry - Solve the following system of equations ...

ALGEBRA 1!PLZ HELP! - Use the Substitution method to solve the system of ...

Math - I am stuck on trying to figure out how to do this question. Could someone...